Development of Octopus Pocket Educational Game Tool to Enhance Children's Fine Motor Skills - Cut Fitriyanti; Jamaliah Hasballah; Hijriati (Sagamedia Teknologi Nusantara, 2023)
This study aims to develop an educational game tool called Kantong Gurita to enhance the fine motor skills of children aged 4-5 years. Fine motor skills involve the coordination of small muscles, especially the fingers and hands, which are crucial for early childhood development. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation) as the framework for the development process. The design focuses on activities such as drawing patterns and tying ropes to train children’s fine motor skills. Validation was conducted by media and subject matter experts to ensure the functionality and safety of the tool. The implementation was carried out in TK Bunga Bangsa Aceh Besar with 12 children aged 4-5 years as participants. Results showed a significant improvement in children’s fine motor skills, with progress from the